Effects of feature-based attention on the motion aftereffect at remote locations - Boynton, Geoffrey M.; Ciaramitaro, Vivian M.; Arman, A. Cyrus (Vision research (Oxford), 2006)
Previous studies have shown that attention to a particular stimulus feature, such as direction of motion or color, enhances neuronal responses to unattended stimuli sharing that feature. We studied this effect psychophysically by measuring the strength of the motion aftereffect (MAE) induced by an unattended stimulus when attention was directed to one of two overlapping fields of moving dots in a different spatial location. When attention was directed to the same direction of motion as the unattended stimulus, the unattended stimulus induced a stronger MAE than when attention was directed to the opposite direction. Also, when the unattended location contained either uncorrelated motion or had no stimulus at all an MAE was induced in the opposite direction to the attended direction of motion. The strength of the MAE was similar regardless of whether subjects attended to the speed or luminance of the attended dots. These results provide further support for a global feature-based mechanism of attention, and show that the effect spreads across all features of an attended object, and to all locations of visual space.